Brassinolides signaling pathway: tandem response to plant hormones and regulation under various abiotic stresses - Yanlong Gao; Xiaolan Ma; Zhongxing Zhang; Xiaoya Wang; Yanxiu Wang (Horticulture Advances)
Abstract Plant hormones play pivotal roles in stress responses by modulating growth, development, stomatal movement, and the expression of stress-related genes, thereby aiding plants in adapting to and managing various environmental challenges. Each hormone exhibits distinct functions and regulatory mechanisms in stress response, with potential complex interactions among them. Brassinosteroids (BRs) represent a novel hormone that influences the expression of its target genes through a series of phosphorylated cascade reactions involving various transcription factors. This signaling pathway regulates diverse growth and development processes in plants. Additionally, BRs interact with other hormones to modulate physiological development. This review examines BRs biosynthesis and metabolism, elucidates the interactions between BRs and abscisic acid (ABA), jasmonic acid (JA), and gibberellins (GA), and explores their roles in regulating responses to drought, salt, cold, and heat. The review underscores the importance of BRs and other hormonal crosstalk in managing nutrient stress, which is vital for understanding plant growth regulation, enhancing crop stress resistance, advancing biotechnology applications, and furthering plant science research. Future research directions and the potential of BRs production and application to improve plant stress resilience are also discussed in the context of current findings.